Konseling individu rational emotive behavior: studi eksperimen terhadap peningkatan konsep diri - Dian Setyowati; Suwarjo Suwarjo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The study aimed to determine the effectiveness of individual counseling to improve the students’ self-concept with the